THE STUDY COMPARISON OF METACOGNITIVE ABILITY BETWEEN INSTAD COMBINED CONCEPT MAP AND CONVENTIONAL LEARNING OF BIOLOGY LEARNING X GRADE STUDENTS AT SMA NEGERI 1 SUKOHARJO IN ACADEMIC YEAR 2012/2013 - Bowo Sugiharto, Ressa Erly A, Riezky Maya P (Pendidikan Biologi, 2015)
The aim of this research was to ascertain metacognitive ability differences between instad combined with concept map and conventional learning of biology learning X grade students SMA Negeri 1 Sukoharjo in academic year 2012/2013.            This research was quasy experiment method. This research design was Post-Test Only with Nonequivalent Control Group Design. The population of this research was all of X grade students at SMA Negeri 1 Sukoharjo in academic year 2012/2013 with 255 students. Sampling techniques used cluster sampling. The sample of this research was class X1 as experiment class with 32 students and class X2 as comparison class with 31 students. The data collected using essay test, observations and school document. The hypotheses was analyzed by t-test.The result of this research showed that t-test of metacognitive ability was significance < 0,05 is 0,015. The average value metacognitive ability of experiment class was 80,85 and comparisan class was 75,94.  The average value metacognitive ability of experiment class was higher than the comparison class.            The research concluded that there was metacognitive ability differences between INSTAD combined with concept map and conventional learning of biology learning grade X student SMA Negeri 1 Sukoharjo in academic year 2012/2013. Keyword: INSTAD, Concept map, Metacognitive ability.